A reappraisal of the governorship of Sir Benjamin D'Urban at the Cape of Good Hope, 1834-1838 - Lancaster, Jonathan Charles Swinburne (Rhodes University, Faculty of Humanities, Department of History, 1981)
Preface: Sir Benjamin D'Urban only spent four years as Governor of the Cape Colony, yet to many people he is one of the most easily identifiable of all British Governors. The principal reason for this, it seems, is the continuing emphasis placed upon his short-lived settlement of the Colony's troublesome eastern frontier in 1835. The main objectives of this thesis have been to examine some of the most notable analyses of that settlement together with an attempt to remove D'Urban's governorship from the narrow and controversial confines imposed by his frontier policy. I have tried to place his governorship in the wider context of his day, examining the various controls upon him, and his overall role as Governor together with some of his administration's less well known but ultimately equally important aspects. In effect, I have tried to view D'Urban in 'the round '. The thesis makes no pretence at being a complete survey. Several important and possibly contributory aspects to a fuller understanding of D'Urban's Cape interlude - notably his ten years in various executive positions in the West Indies and British Guiana, and his period as commander-in-chief of the British army in Canada - were beyond the reach of anything more than a cursory review. Presumably there are documents relative to this period of D'Urban's life in the Archives in Montreal, Georgetown and London. D'Urban's reputation in South Africa continues to rest upon the short-lived system he established in 1835 and the great promise for future relations between black and white that many authors then and since saw in it, or alternately failed to see in it. With this in mind, and the realisation that 145 years and a succession of Governors, High Commissioners and Prime Ministers have passed since 1835, the following extract from the front page of The Daily Dispatch of 10 May, 1980, is revealing. It was reported that the Ciskei government demanded "all the land between the Kei and Fish Rivers, the Indian Ocean and the Stormberg Mountains to form the territory of an independent Ciskei ." The fundamental questions of to whom the land belongs and of how to establish a just modus vivendi with the Xhosa, which plagued both D'Urban's short administration and the Colonial Office for much of the Nineteenth Century are still with us today. Any analysis of his four year period as Governor of the Cape must necessarily be tempered by this realisation.
Keywords: D'Urban, Benjamin, Sir, 1777-1849; Colonial administrators -- South Africa -- Cape of Good Hope; Cape of Good Hope (South Africa) -- History -- 1795-1872